α-Synuclein-Induced NOX2 Activation in Microglia: Signaling Mechanisms and Implications for Parkinson’s Disease - Mattsson, Axel (My University, 2026)
Parkinson’s disease (PD) is the second most common neurodegenerative disease and is characterized by progressive loss of dopaminergic neurons. Several mechanisms have been proposed to contribute to neuronal degeneration, including accumulation of α-synuclein (α-syn) fibrils, oxidative stress, and neuroinflammation. α-syn fibrils can activate microglia, the brain-resident immune cells, which produce reactive oxygen species (ROS) through NADPH Oxidase 2 (NOX2), an enzyme implicated in PD-associated neuroinflammation. This study investigated whether different fibrillar α-syn variants differentially induce microglial ROS production and the underlying signaling pathways associated with NOX2 activation. Additionally, NOX2-associated transcriptional signatures were investigated in single-cell data from midbrains of healthy controls and PD patients. The results demonstrated that fibrillar α-syn induced NOX2-dependent ROS production in murine microglial models, whereas no ROS response was observed in human Induced pluripotent stem cell (iPSC)-derived microglia even though a pro-inflammatory state is induced, suggesting model and activation state dependence. Experiments targeting inflammatory mediators suggested involvement of Bruton’s tyrosine kinase (BTK)-, protein kinase B (Akt)-, and protein kinase C (PKC)-dependent pathways in α-syn-induced NOX2 activation. Furthermore, neuron-like cells were susceptible to NOX2-derived ROS and activated microglia in PD showed trends toward increased NOX2- and oxidative stress associated transcriptional signatures. Overall, these findings support a potential role for microglial NOX2-associated signaling in PD pathophysiology.